Observations of Hydration and Dehydration in the Winter 2000 Arctic Stratosphere - Herman, R.; Webster, C.; Ordla, K.; Bui, P.; Gandrud, B. (2004)
During the January 2000 deployment of the SAGE III Ozone Loss Validation Experiment (SOLVE), the NASA ER-2 aircraft intercepted air parcels with unusual water mixing ratios within the the Arctic polar vortex.